The images of Lithuania in the popular literature of 1990s - Vaičiūtė, Deimantė (Vilnius University Open Series, 2024)
The article proposes a cultural history perspective, where popular literature is interpreted as a historical source. The genres, aesthetics and themes of these authors’ writing differ, which gives an opportunity to see the problematic diversity of the period, what was topical and what challenges society faced during the period in question: I. Buivydaitė focuses on love/family experiences, E. Malūkas writes about illicit life and sects, E. Kalėda focuses on criminal groups, and J. Ivanauskaitė focuses on the image of women and the journey of spirituality. The descriptive themes are analysed in the article, comparing to what extent the plot reflects the environment and to what extent it is a complete fiction.